The language of modern news and the timelessness: reforming journalism in the non-occidental world (Bahasa berita moden dan keabadian: reformasi kewartawanan di dunia bukan oksidental) - Ahmad Murad Merican, (Institut Islam Hadhari Universiti Kebangsaan Malaysia, 2011)
The ethos of news, commentary and journalism as an institution needs to be transformed in embracing the dimensions of timelessness and the transcendent. This article suggests that the current practice of not recognizing the incompatibility between the language of religion, as represented by Islam and the language of the media, and as represented by the institution of journalism need to be reviewed. It focuses on the product, not the whole profession. The news and the modern institution and profession of journalism are not a universal phenomena. It is unique to the Occidental world. It argues that the language of news and the language of religion are two separate, incompatible paradigms, hence suggesting overcoming that incompatibility. This article argues for a rethinking and a reevaluation on the reportage of Islam and religion in the non-Occidental world.